Continuous Flow Synthesis of Non‐Symmetrical Ureas from CO2. Issue 3 (20th January 2023) - Labiche, Alexandre; Norlöff, Maylis; Feuillastre, Sophie; Taran, Frederic; Audisio, Davide
Abstract: We report on a continuous flow synthetic process of non‐symmetrical ureas, based on the implementation of a Staudinger/aza‐Wittig reaction sequence. This flow technology allows obtaining the key urea functional group directly from the fundamental C1 building block CO2 . A library of 26 derivatives, including alkyl/alkyl, alkyl/aryl and aryl/aryl ureas could be synthesised. In addition, the method was also suitable for the synthesis of S ‐thiocarbamates. The potential for large‐scale reaction implementation and a first application to continuous flow 13 C‐isotope labeling are shown. Abstract : A continuous flow synthesis of non‐symmetrical ureas, based on the implementation of the Staudinger/aza‐Wittig reaction sequence is reported. The potential for large‐scale reactions was demonstrated and a first application to 13 C‐isotope labeling was also described.